GREEN PURCHASING BEHAVIOR: PREFERENCES, ATTITUDES AND SOCIAL VALUES - Ali, Hapzi; Octavia, Ade; Sriayudha, Yayuk (Dinasti International Journal of Digital Business Management, 2022)
The Literature Review article on Environmentally Friendly Purchasing Behavior: Preferences, Attitudes and Social Values is a scientific article that aims to build a research hypothesis on the influence between variables that will be used in further research, within the scope of Marketing Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this Literature Review article are that: 1) Preference has an effect on Environmentally Friendly Purchasing Behavior; 2) Attitudes influence Environmentally Friendly Purchasing Behavior; and 3) Social Values have an effect on Environmentally Friendly Purchasing Behavior. Apart from these 3 exogenous variables that affect the endogenous variable Environmentally Friendly Purchasing Behavior, there are still many other factors including Environmental Knowledge, Ecolabelling and Consumer Trust variables.